Six weeks to live : a novel - McKenzie, Catherine (Atria Books, 2021)
"Jennifer Barnes never expected the shocking news she received at a routine doctor's appointment: she has a terminal brain tumour-and only six weeks left to live. While stunned by the diagnosis, the forty-eight-year-old mother decides to spend what little time she has left with her family-her adult triplets and twin grandsons-close by her side. But when she realizes she was possibly poisoned a year earlier, she's determined to discover who might have tried to get rid of her before she's gone for good. Separated from her husband and with a contentious divorce in progress, Jennifer focuses her suspicions on her soon-to-be ex. Meanwhile, her daughters are each processing the news differently. Calm medical student Emily is there for whatever Jennifer needs. Moody scientist Aline, who keeps her mother at arm's length, nonetheless agrees to help with the investigation. Even imprudent Miranda, who has recently had to move back home, is being unusually solicitous. But with her daughters doubting her campaign against their father, Jennifer can't help but wonder if the poisoning is all in her head-or if there's someone else who wanted her dead"--